Validade estrutural da versão brasileira do neck bournemouth questionnaire em indivíduos com dor cervical crônica - ARAUJO, Gabriel Gardhel Costa (2022)
Objective: To perform the structural validity of the Brazilian version of the Neck Bournemouth Questionnaire (NBQ) in patients with chronic neck pain based on factor analysis. Materials and Methods: This study was approved by the Research Ethics Committee of the institution (protocol number 2,383,607). Data were collected through an online platform (Google forms, Mountain View, CA, USA) with individuals living in the state of Maranhão, northeastern Brazil. The dissemination of this research was carried out through social media and mobile messaging applications. The minimum sample size of 100 participants was adopted based on international recommendations. Inclusion criteria were: individuals with the Brazilian Portuguese as the mother tongue, of both sexes, aged 18 years or older, with neck pain for at least 3 months (chronic). In addition, all participants presented a minimum score of 3 points on the Numerical Pain Scale (NPS). To characterize the sample, other assessment instruments related to neck pain were applied: the EDT was used to measure pain intensity; The Neck Disability Index (NDI) was used to measure neck pain-related disability; the Pain-Related Catastrophizing Thoughts Scale (PCTS) was used to measure catastrophising; and the Tampa Scale for Kinesiophobia (TSK) was used to measure pain-related kinesiophobia. In addition to these instruments, the NBQ was applied. Results: A total of 199 individuals were recruited for the present study. Of these, 103 participants were included in the study. The sample consisted mostly of adults over 30 years of age, female, thin, single and with complete higher education. Regarding the analysis of the internal structure of the NBQ, exploratory factor analysis was initially performed with the implementation of parallel analysis to identify how many dimensions the instrument had. Thus, with a Kaiser-Valor value of Meyer-Olkin of 0.80 and significant Bartlett test (p<0.05), a one-dimensional structure of the NBQ was identified. Thus, 4 possibilities of internal structure of the NBQ (Models 1, 2, 3 and 4) were tested. All models presented a high amount of residues, identified by the value of Root-Mean-Square Error of Aproximation > 0.08 and chi square/degree of freedom > 3.00. In addition, Model 1 presents inadequate values for the Tucker-Lewis Index and Standardized Root Mean Squared Residual. In summary, we observed a structure of the NBQ not supported by the statistical procedures used here. Conclusion: The Brazilian version of the NBQ does not present well-defined internal structure. That is, it was not possible to identify the construct measured by the instrument in individuals with chronic neck pain.